Collisional cooling of primordial and interstellar media by H2. Issue 3 (6th August 2021) - Flower, D R; Pineau des Forêts, G; Hily-Blant, P; Faure, A; Lique, F; González-Lezana, T
ABSTRACT: We have computed the rate of collisional cooling of a gas by H2 molecules under conditions appropriate to the primordial and interstellar media. We incorporated the results of recent calculations of the rate coefficients for collisional excitation of H2 by H and H +, which are essential to a reliable evaluation of the ortho : para H2 ratio and the cooling rate. Comparison is made with the results of previous calculations of the cooling function. The data are made available for grids of values of the kinetic temperature, density, H:H2 ratio, and the fractional abundance of H +, together with a programme to perform linear interpolation of the data sets for any given set of values of these parameters, within the ranges of the grids.